2015
DOI: 10.1038/srep12816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Outcomes among Patients with Polycystic Kidney Disease on Hemodialysis and Peritoneal Dialysis

Abstract: Polycystic kidney disease (PCKD) is the most common hereditary cause of end-stage renal disease, the complications of which may prevent the choice of peritoneal dialysis (PD). The aim of this study was to explore the effects of dialysis modality on outcomes in patients with PCKD. We extracted a cohort of 1417 adult patients with PCKD initiating long-term dialysis therapy in 1999–2010 from the Taiwan National Health Insurance Research Database, among which 125 patients chose PD. The patients on HD were older an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 25 publications
(41 reference statements)
0
41
0
Order By: Relevance
“…After exclusion of irrelevant studies and duplicates, 24 potentially eligible studies were deeply screened. Eventually, eight studies involving 7685 PKD patients were included for final meta‐analysis . Characteristics of included studies were listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusion of irrelevant studies and duplicates, 24 potentially eligible studies were deeply screened. Eventually, eight studies involving 7685 PKD patients were included for final meta‐analysis . Characteristics of included studies were listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The follow‐up duration ranged from 3 years to 22 years . Two studies were performed in Europe, five studies were in Asia, and one study in America. The patients in PD group included continuous ambulatory peritoneal dialysis (CAPD) and automated peritoneal dialysis (APD) modalities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The all-cause mortality between patients with PKD on PD and HD 4 studies [19,25,39,40] with a total of 5, 762 patients reported the all-cause mortality between patients with PKD on PD and HD. The all-cause mortality did not differ between the PKD patients on PD and HD (RR: 0.87, 95%CI: 0.72-1.06) with no heterogeneity (I 2 =7.7%, P=0.355) (Fig.…”
Section: The All -Cause Mortality In Pkd and Non-pkd Patients On Pdmentioning
confidence: 99%
“…The main features of the studies on the adverse outcomes for all articles in Table 1. 7 studies [16-19, 21, 24, 39] were conducted in Europe, with the exception of seven [9,20,22,23,25,26,40] conducted in Asia. Patients' age in PKD ranged from 35.4 to 63.6 years old, however, patients' age in non-PKD was higher than PKD, ranged from 46 to 61 years old.…”
Section: Literature Searchmentioning
confidence: 99%